Agreement Between Physician Evaluation and the Composite Response Index in Diffuse Cutaneous Systemic Sclerosis. Issue 11 (12th July 2022) - Zheng, Boyang; Wang, Mianbo; McKenna, Kerry; Shapiro, Lee; Silver, Richard; Csuka, Mary Ellen; van den Hoogen, Frank; Robinson, David; Pauling, John D.; Hummers, Laura; Krieg, Thomas; Del Galdo, Francesco; et al.
Abstract : Objective: Diffuse cutaneous systemic sclerosis (SSc) is a highly heterogeneous disease. A provisionally approved Composite Response Index in diffuse cutaneous SSc (CRISS) was developed as a 1‐year outcome measure for clinical trials. Our goal was to further validate the CRISS by examining agreement between CRISS definitions for improved/non‐improved with physicians' evaluation of disease. Methods: Patient profiles from a large observational cohort were created for 50 random diffuse cutaneous SSc patients of <5 years disease duration with improved CRISS scores after 1 year and 50 with non‐improved CRISS scores. Profiles described disease features used during the initial CRISS development at baseline and at 1 year. Each profile was independently rated by 3 expert physicians. Majority opinion determined whether a patient was improved or not improved, and kappa agreement with the CRISS cutoff of 0.6 was calculated. Results: Patients had mean ± SD disease duration of 2.2 ± 1.3 years. There was substantial agreement between the physician majority opinion about each case and the CRISS (κ = 0.76 [95% confidence interval (95% CI) 0.64–0.88]). The agreement between each individual physician opinion and the CRISS was also substantial (κ = 0.70 [95% CI 0.62–0.78]). All CRISS non‐improvers were also rated as non‐improved by physician majority; however, 12 CRISS improvers were rated as non‐improved by physicians. Conclusion: There was substantial agreement between the dichotomous CRISS rating and physician assessment of diffuse cutaneous SSc patients after 1 year. This supports the use of a CRISS cutoff at 0.6 for improvement versus non‐improvement, although the CRISS tended to rate more patients as improved than did physicians.